Physical Activity for Aboriginal Older Adults: A Scoping Study and a Case Study - Brooks-Cleator, Lauren (Université d'Ottawa / University of Ottawa, 2014)
In Canada, out of the total Aboriginal populations, the older Aboriginal adult populations continue to increase and suffer disproportionately poor health compared to non-Aboriginal seniors. Despite these facts, there is a dearth of research concerning Aboriginal older adults, especially regarding their engagement with physical activity. My thesis is written in the publishable paper format and is comprised of two papers. Using a scoping study methodology in paper one, I demonstrate that intersecting factors such as colonialism, social inequities, and physical activity practices that are rooted in Western ideals and do not address Indigenous older adults’ needs, all contribute to Indigenous older adults’ lack of participation in physical activity. Using a case study approach in paper two, I demonstrate how Elders In Motion, a program offered by the Northwest Territories Recreation and Parks Association (NWTRPA), shows a shift in physical activity programs becoming more respectful of older Aboriginal adults’ cultures and communities; however, while the staff at the NWTRPA has made a strong effort to adapt a southern-based program for northern communities in the NWT, there are several program features that reaffirm colonial practices and support Westernized ideas of physical activity. Taken together, the papers in this thesis make apparent that physical activity programs and research concerning physical activity for older Aboriginal adults continue to be embedded in colonial practices. As a result, there is a demonstrated need for program development and research in this area to work towards reducing health disparities and challenging colonial practices.